Clinical performance validation and four diagnostic strategy assessments of high-sensitivity troponin I assays - Junyi Wu; Yaotong Hua; Yilin Ge; Ke Chen; Siyu Chen; Jiashu Yang; Hui Yuan (Scientific Reports)
Abstract Acute coronary syndrome (ACS) includes conditions such as unstable angina (UA), non-ST elevation myocardial infarction (NSTEMI), and ST elevation myocardial infarction (STEMI). High-sensitivity cardiac troponin I (hs-cTnI) assays have been recommended as primary biomarkers for NSTEMI diagnosis due to their high sensitivity and specificity. However, there is no consensus on the optimal diagnostic strategy for early NSTEMI detection. This study aims to evaluate the diagnostic performance of four hs-cTnI-based strategies for suspected NSTEMI: Limit of Detection (LoB), Single Cut-off, hs-cTnI 0/1 h Algorithm, and hs-cTnI 0/2 h Algorithm, in a Chinese cohort and compare the performance of assays from different manufacturers. Performance verification was conducted, including LoB, LoD, LoQ, and precision analysis. Clinical samples from 267 ACS patients were analyzed using Hybiome hs-cTnI assays. Diagnostic accuracy was assessed based on sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and F1-score. The LoB strategy demonstrated 100% sensitivity but low PPV (14.0%). Both the hs-cTnI 0/1 h Algorithm and hs-cTnI 0/2 h Algorithm showed high diagnostic performance, with the 0/2 h algorithm providing the best overall. 89.0% accuracy, 93.3% sensitivity, and 73.68% F1-score. The hs-cTnI 0/2 h Algorithm offers the most reliable diagnostic performance for early NSTEMI diagnosis.